Skid control enhancement for small electric vehicle by using sliding mode control strategy - S.M., Asyraf; Mohamad Heerwan, Peeie; Muhammad Izhar, Ishak (IEEE, 2018)
Small electric vehicle (EV) with two in-wheel motors employed hydraulic brake system at the front tires and mechanical brake system at the rear tires. The mechanical brake system is installed at the rear tire due to the space limitation for the hydraulic brake system. Although mechanical brake system is compact, the response performance of mechanical brake system is lower than hydraulic brake system. During braking in slippery condition, the stability and safety of small EV will be lost. In this study, to enhance the braking performance of small EV, the sliding mode control (SMC) approach is proposed. The slip ratio is used in the SMC control method to determine the sliding condition of the vehicle. If the slip ratio is not in the optimum range, the SMC will be activated to control the valve in the hydraulic control unit. Based on the signal from the SMC, the valve will open or close to increase, decrease or hold the brake pressure. The analysis has been done in the Matlab Simulink and the result shows that by using SMC, the tires were not lockup and the slip ratio is in the optimum range.